2007
DOI: 10.1152/japplphysiol.00066.2007
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte-colony stimulating factor enhances muscle proliferation and strength following skeletal muscle injury in rats

Abstract: Insufficiency of skeletal muscle regeneration often impedes the healing process with functional deficiencies and scar formation. We tested the hematopoietic growth factor granulocyte-colony stimulating factor (G-CSF) with respect to its efficacy to improve functional muscle regeneration following skeletal muscle injury in Wistar rats. After crush injury to the left soleus muscle, animals received daily G-CSF (20 mug/kg ip) or vehicle solution (n = 30 per group each). Sham-operated animals without muscle injury… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
53
2
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 44 publications
4
53
2
1
Order By: Relevance
“…Upon a 20-min stabilization period after completion of surgery, in vivo microscopy of the soleus muscle was performed, as previously described for the EDL. [14][15][16][17] To consider the heterogeneous morphology of the traumatized muscle, a classification system, as recently published by our group 18 was used, considering three zones. Zone 1 (z1) was defined as the central muscle area with entrance of the neurovascular structures.…”
Section: Animal Model and Experimental Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon a 20-min stabilization period after completion of surgery, in vivo microscopy of the soleus muscle was performed, as previously described for the EDL. [14][15][16][17] To consider the heterogeneous morphology of the traumatized muscle, a classification system, as recently published by our group 18 was used, considering three zones. Zone 1 (z1) was defined as the central muscle area with entrance of the neurovascular structures.…”
Section: Animal Model and Experimental Groupsmentioning
confidence: 99%
“…Thus, muscle regeneration might benefit from adjunct pharmacological strategies, like application of G-CSF 18 and EPO, presumably through mobilization of cells, which will subsequently help to regenerate more intensely and rapidly [38][39][40] or through extracellular signals. 5 In line with this view, EPO caused an increase not only of the number of BrdU-positive satellite cells but also of interstitial cells with finally improved muscle contraction capacity when compared to vehicle-treated injured animals.…”
mentioning
confidence: 99%
“…1 Previous studies have examined the use of drugs, cytokines, cells, and gene therapy attempted to improve muscle recovery. [2][3][4][5][6][7][8][9][10] Recently, we showed that transplantation of human peripheral blood CD133-expressing cells (CD133 + cells) inhibits fibrosis and improves muscle regeneration after skeletal muscle laceration. 11 Human blood CD133 + cells are wellsuited for clinical applications, because collecting these cells is safe, with limited ethical problems.…”
mentioning
confidence: 99%
“…In our previous screen for myocyte differentiationpromoting factors 6,7 , we noted markedly elevated expression of granulocyte colony-stimulating factor receptor (G-CSFR, encoded by csf3r) in the developing somite 8 . Furthermore, G-CSFR was transiently expressed in regenerating myocytes of adult injured skeletal muscle, and extrinsic G-CSF supported short-term muscle regeneration in cardiotoxin-induced skeletal muscle injury 9 and crush injury 10 . However, although we found high G-CSFR expression in regenerating immature myocytes, whether G-CSFR would be expressed in SCs and whether G-CSF signalling would affect the SC population in skeletal muscle remain unclear.…”
mentioning
confidence: 96%